The Development of Educational Youtube Videos-Based Instructional Material for Speaking for Beginner Course - Zahro, Syifa' Khuriyatuz; Tasaufy, Farid Shiddiq (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
An analysis of the students’ needs demonstrated that there is no primary instructional material of speaking for beginner utilized in the classroom. In addition, both lecturers and students preferred the utilization of an authentic audio-visual material like YouTube videos rather than a traditional material taken from textbook to accelerate their speaking proficiency. The current study sought to develop educational YouTube videos-based instructional material of speaking for beginner course through Borg & Gall model that cover three main stages out of ten stages; preliminary research, model development, and model validation. Fifty-nine students who attended speaking for beginner course of three universities in Lamongan; Darul Ulum Islamic University, Billfath University, and the Islamic University of Lamongan participated in the try-out stage. Three kinds of Instruments are questionnaire and interview guidance that were adapted from Djahida, while validation checklist was adopted from Beaudin and Balasubramanian, Shetty & Sathyanarayana. The instrucional material developed in this study is so-titled ‘Speaking for Beginner: A way to speak like natives’. The acceptability revealed in the students’ evaluation at the try-out demonstrates that, the material was generally good and acceptable for the students and the lecturers. Such results bring about the conclusion that ‘Speaking for Beginner: A way to speak like natives’ is suitable and applicable to the speaking for beginner classroom.